The Talent Training Mode of International Service Design Using a Human–Computer Interaction Intelligent Service Robot From the Perspective of Cognitive Psychology - Yang, Yayun (Frontiers in Psychology, 2021)
In order to effectively improve the efficiency of international service design talent training, make it more in line with the needs of society, first, the current status of international service design talent training and its professional training focus are analyzed. Based on the above problems, from the perspective of cognitive psychology, artificial intelligence and human-computer interaction (HCI) technology are used to construct the international service design talent training mode of HCI intelligent service robot. This mode can be used to solve the existing teaching problems by using novel means to ensure the quality of teaching. Finally, through the actual analysis of teaching cases, the effectiveness of the proposed talent training mode is verified. It is found that the HCI system is based on the knowledge of cognitive psychology. According to the characteristics and functions of educational robot, the robot is combined with traditional teaching activities, and the robot assisted talent training mode is designed. Robot assisted talent training is a feasible training method, which can improve the efficiency of talent training. Students have confidence in their learning skills before the course, and the confidence is further strengthened after the end of the course. After the course, the students have a stronger sense of cooperation. This study can provide theoretical ideas for the research of international service talent training mode.